Ethical Utilization of Mobile Banking In Enhancing Digital Economic Literacy: An Islamic Banking Perspective - Choiriyah Choiriyah; Dwi Noviani; Saprida Saprida (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2026)
This study examines the utilization of Islamic mobile banking applications as a medium for enhancing digital economic literacy within an Islamic ethical framework. Using a descriptive quantitative approach, questionnaires were distributed to 100 active users of Islamic mobile banking applications in Indonesia. Data were analyzed using descriptive statistics, Pearson correlation, and simple linear regression to assess the relationship between educational features, perceived Islamic banking ethics, and users’ digital economic literacy. The findings indicate that educational features and the perceived integration of Islamic ethical values—such as justice, transparency, and the avoidance of riba—are significantly associated with higher levels of digital economic literacy. However, only a limited proportion of users actively access Sharia-based educational content within the applications. This suggests that while Islamic mobile banking has strong potential as an ethical learning platform, its effectiveness depends on the clarity, accessibility, and interactivity of Sharia-oriented educational features.